2021
DOI: 10.1200/go.20.00458
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Acceptability of Breast Reconstruction Among Women With Breast Cancer: A Prospective Survey

Abstract: PURPOSE Quality of life has become an integral aspect of the management of breast cancer. Many women still need to undergo a modified radical mastectomy (MRM). Factors affecting the choice a woman makes to undergo breast reconstruction (BR) are unclear and are hypothesized to be influenced by socioeconomic factors. We conducted a survey to evaluate the awareness and acceptability of BR among women with breast cancer at our institution. METHODS A novel questionnaire was designed and served to 3 groups of women:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…The intraoperative tumour clearance rate is high, and the patients have less intraoperative bleeding and smaller incisions, indicating higher surgical safety. It has more advantages in the treatment of breast cancer compared to MRM group 25 . The results of this study showed that the overall incidence of complications such as upper limb oedema, subcutaneous haematoma and incision infection in patients treated with BCS group was 93.48% (43/46), significantly lower than the rate of 50% (21/42) in patients treated with MRM group and the difference was statistically significant ( p < 0.001).…”
Section: Discussionmentioning
confidence: 62%
“…The intraoperative tumour clearance rate is high, and the patients have less intraoperative bleeding and smaller incisions, indicating higher surgical safety. It has more advantages in the treatment of breast cancer compared to MRM group 25 . The results of this study showed that the overall incidence of complications such as upper limb oedema, subcutaneous haematoma and incision infection in patients treated with BCS group was 93.48% (43/46), significantly lower than the rate of 50% (21/42) in patients treated with MRM group and the difference was statistically significant ( p < 0.001).…”
Section: Discussionmentioning
confidence: 62%
“…Western countries, BCS rates are 60%−70%. 33 Rates of breast reconstruction following mastectomy varied between 0% 23 and 14.1%., 18 with rates highest in India (14.1%) 18 than other South…”
Section: Rates Of Breast Surgery and Reconstructionmentioning
confidence: 97%
“…Breast reconstruction rates were calculated as the total number of patients who opted for breast reconstruction divided by the total number of patients in the sample. 5,7,[18][19][20][21][22][23][24] Qualitative data on attitudes of patients was obtained from review of data tables or figures from included papers or extracted directly from the text of the article (often including direct patient quotes). Some studies organized their article by themes the authors felt illustrated South Asian attitudes, and these sections were reviewed to note thematic trends that define the experience of South Asian patients toward breast reconstruction, breast cancer, and breast cancer survivorship.…”
Section: Data Collectionmentioning
confidence: 99%
“…Combining mastectomy with plastic surgery for reconstruction, aimed at restoring volume, shape, and contour, can help mitigate the psychological impact and enhance women's self-esteem. [2][3][4] Breast reconstruction yields several benefits, including the restoration of femininity, bodily integrity, and rehabilitation from postoperative complications, ultimately improving physical, emotional, and social well-being. 5 Several factors influence the acceptance of breast reconstruction among breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%